Pendekatan Pembelajaran Kontekstual Dalam Meningkatkan Pemahaman Materi Ilmu Pengetahuan Alam Pada Tingkat Sekolah Dasar - Siti Muakhiroh (Publikasi Indonesia, 2022)
Quality education is the right of every community, including elementary school students. Elementary school as a basic education level must be able to instill the character of a learner's soul in students so that students are able to understand the material presented in class, especially in science learning which is learning to be close to nature. Unfortunately, all this time, science learning is still conventional as in 5th grade science learning in an elementary school in Ponorogo Regency. For this reason, researchers want to find out more about the contextual learning approach in improving understanding of Natural Science (IPA) material at the elementary school level. The purpose of this study is to determine whether or not there is an increase in understanding of science after contextual learning is implemented in elementary school. The research method used is descriptive qualitative with a sample of class 5 totaling 35 people. Based on the results of the study, it was found that there was an increase in the average grade after the contextual learning was implemented, from 67.6 to 78.03. In addition, the number of students who reached the KKM also increased by 60%, from 20% to 80%. With this, the contextual approach can improve understanding of science material at the elementary level.